2002
DOI: 10.1056/nejmoa020150
|View full text |Cite
|
Sign up to set email alerts
|

Response to Imatinib Mesylate in Patients with Chronic Myeloproliferative Diseases with Rearrangements of the Platelet-Derived Growth Factor Receptor Beta

Abstract: Imatinib mesylate induces durable responses in patients with chronic myeloproliferative diseases associated with activation of PDGFRB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
343
0
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 582 publications
(355 citation statements)
references
References 22 publications
7
343
0
5
Order By: Relevance
“…Patients with these fusion genes have been reported to achieve rapid hematologic, cytogenetic, and molecular responses with imatinib therapy. 40,41 However, none of our patients had any abnormality involving chromosome 5q33 and none had eosinophilia, a common feature among patients with these fusion genes. Similar results were reported by Raza et al 42 in patients without PDGF-R fusion genes.…”
Section: Discussionmentioning
confidence: 63%
“…Patients with these fusion genes have been reported to achieve rapid hematologic, cytogenetic, and molecular responses with imatinib therapy. 40,41 However, none of our patients had any abnormality involving chromosome 5q33 and none had eosinophilia, a common feature among patients with these fusion genes. Similar results were reported by Raza et al 42 in patients without PDGF-R fusion genes.…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, patients with myeloproliferative disorders carrying FIP1L1/PDGFRa and activated forms of PDGFRb were also successfully treated with IM (Apperley et al, 2002;Cools et al, 2003). In addition, IM was proven to be effective against cells transfected with TEL/ABL (Carroll et al, 1997).…”
Section: Facilitation Of Genomic Instabilitymentioning
confidence: 99%
“…48 Other PDGFR␤ fusion partners also have been described, and it has been reported that imatinib is effective in some patients with these fusion genes. 49 2) The fusion gene FIP1L1-PDGFR␣ has been demonstrated in 9 of 16 (56%) patients with idiopathic hypereosinophilic syndrome (HES), leading to the constitutive activation of PDGFR␣ kinase in the neoplastic clone. In vitro studies of the effect of imatinib mesylate on the growth of Ba/F3 cells that expressed FIP1L1-PDGFR␣ showed that they were inhibited efficiently by much lower concentrations of imatinib than Ba/F3 cells that expressed BCR-ABL (50% inhibitory concentration, 3.2 nM vs. 582 nM, respectively).…”
Section: Constitutively Active Kinases As Targets Of Therapymentioning
confidence: 99%